Omega-3 and poly-unsaturated fatty acids-enriched hamburgers using sterol-based oleogels - Martins, Artur J. (2019)
Obesity and cardiovascular diseases are among the most worrying health problems worldwide. Dietary habits can be catalysts for the uprising of these health issues in western countries. In this work, a meat product (pork patties) that is commonly elaborated with a high fraction of saturated fat was reformulated with an oleogel based on linseed oil (rich in polyunsaturated fatty acids). The oleogel was used for the partial replacement of the solid fat fraction present in pork patties (H-25 for 25% and H-75 for 75% of replacement). Incorporation of oleogels resulted in the modification of the fatty acid profile and in the significant decrease of the omega-6/omega-3 ratio. Results showed that for both degrees of fat substitution there were no differences between the patties produced with oleogel incorporation and the control, regarding textural parameters such as hardness, cohesiveness and chewiness. Overall, samples with less amount of oleogel (H-25) were well classified in the acceptance and preference tests, despite of the clear preference among the sensorial panel towards the control samples. These results show the feasibility of introducing oleogels as a fat replacer in the manufacturing process of pork patties, though there is still work to be done regarding some of their sensorial attributes. This article is protected by copyright. All rights reserved